X-ray Micro-Computed Tomography of Polymer Electrolyte Fuel Cells: What is the Representative Elementary Area?. Issue 1 (22nd January 2020) - Hack, Jennifer; García-Salaberri, Pablo A.; Kok, Matthew D. R.; Jervis, Rhodri; Shearing, Paul R.; Brandon, Nigel; Brett, Dan J. L.
Abstract : With the growing use of X-ray computed tomography (X-ray CT) datasets for modelling of transport properties, comes the need to define the representative elementary volume (REV) if considering three dimensions or the representative elementary area (REA) if considering two dimensions. The resolution used for imaging must be suited to the features of interest in the sample and the region-of-interest must be sufficiently large to capture key information. Polymer electrolyte fuel cells have a hierarchical structure, with materials spanning multiple length scales. The work presented here examines the nature of the REA throughout a 25 cm 2 membrane electrode assembly (MEA), focusing specifically on the micron length scale. Studies were carried out to investigate key structural (volume fraction, layer and penetration thickness, pore diameters) and transport (effective diffusivity) properties. Furthermore, the limiting current density of the nine regions was modelled. Stochastic heterogeneity throughout the sample results in local variations throughout. Finally, effects of resolution were probed by imaging using a range of optical magnifications (4× and 20×). The correlated and competing effects of voxel resolution and sampling size were found to cause difficulties where loss of clarity in the boundaries between phases occurs with larger imaging volumes.